Thermal decomposition of the acetone cyclic diperoxide in 1-octanol solution - Leiva, Laura A. C. (2008)
The thermal decomposition reaction of acetone cyclic diperoxide (ACDP) in 1-octanol (OCT) solution, at the temperatures and initial concentration ranges of 130° -166 ºC and (0.94-3.00) x 10-2 mol/L , respectively, follows a pseudo-first order kinetic law. Acetone is the main organic decomposition product observed. The activation parameters values of the initial reaction step (ΔH# = 25.8 ± 0.3 kcal/mol; ΔS# = -19.1 ± 0.6 cal/mol K; Ea = 26.6 ± 0.3 kcal/mol), support a reaction mechanism which includes a homolytic rupture of one peroxidic bond of the ACDP molecule with participation of the solvent and involving a biradical intermediate.